Pengembangkan Ketrampilan Soft Skill Santri di Pondok Pesantren Tahfizh Wadil Quran Tangerang - Amaliyah; Merdeka, Muhamad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Islamic boarding schools have a role in education, especially studying religious sciences among students. Also development in the knowledge aspect. Attention to soft skills which include students' personal and interpersonal abilities is also carried out. Soft skills are skills such as communication, leadership, teamwork, critical thinking, negotiation, persuasion, time management and adaptation. This ability is very important in everyday life for students. Learning soft skills for students to improve mentality in the form of character and humanism in the Islamic boarding school environment. The Tahfidz Wadil Quran Islamic boarding school uses direct practice, in daily activities and tahfidz learning at the Islamic boarding school.